2014
DOI: 10.1128/aem.00430-14
|View full text |Cite
|
Sign up to set email alerts
|

From Metagenomics to Pure Culture: Isolation and Characterization of the Moderately Halophilic Bacterium Spiribacter salinus gen. nov., sp. nov

Abstract: bRecent metagenomic studies on saltern ponds with intermediate salinities have determined that their microbial communities are dominated by both Euryarchaeota and halophilic bacteria, with a gammaproteobacterium closely related to the genera Alkalilimnicola and Arhodomonas being one of the most predominant microorganisms, making up to 15% of the total prokaryotic population. Here we used several strategies and culture media in order to isolate this organism in pure culture. We report the isolation and taxonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 52 publications
6
58
0
Order By: Relevance
“…Number related species or genera within the family Ectothiorhodospiraceae are present and await classification [16 ].…”
Section: Datasetsmentioning
confidence: 99%
“…Number related species or genera within the family Ectothiorhodospiraceae are present and await classification [16 ].…”
Section: Datasetsmentioning
confidence: 99%
“…This has prevented the scientific community from studying and understanding the primary relationships and functions of microbes in these natural environments. León et al, 2014), which indicated that this genus is very abundant in these environments. However, a closer look at these contigs revealed that some of them had low similarity to the genomes of S. salinus and S. curvatus, while still being syntenic to them.…”
mentioning
confidence: 97%
“…Moreover, studies using culture-independent techniques for the analysis of the microbial diversity dwelling in saltern ponds of intermediate salinity have shown that the most abundant microbes have not been retrieved in axenic cultures yet, possibly due to their slow growing time and particular requirement of nutrients being very different to the ones commonly used in laboratory studies (Ghai et al, 2011;Fern andez et al, 2014a, b). This has prevented the scientific community from studying and understanding the primary relationships and functions of microbes in these natural environments.Recently, León et al (2014) described the genus Spiribacter to accommodate an abundant moderate halophile thriving in intermediate-salinity saltern ponds as ascertained by metagenomic assemblies and recruitment analysis. It belongs to the family Ectothiorhodospiraceae, within the order Chromatiales, class Gammaproteobacteria in the phylum Proteobacteria.…”
mentioning
confidence: 99%
See 2 more Smart Citations